Ultralow-dosage composite nano early strength agent and preparation method thereof

By using ultra-low doping in composite nano-premature strength agents, stable dispersion and connection between nano-hydrated calcium silicate and C-S-H gel is achieved through the reaction and pH adjustment of nano-silica sol and silane-modified polycarboxylic acid, the stable dispersion and connection of nano-hydrated calcium silicate and C-S-H gel is achieved through the reaction and pH adjustment of nano-hydrated calcium silicate and C-S-H gel , solves the problems of high dosage and insufficient early strength in the prior art, significantly improves the early and late strength of concrete, and is suitable for industrial applications.

CN119192595AActive Publication Date: 2024-12-27GUANGZHOU INSTITUTE OF BUILDING SCIENCE CO LTD

Patent Information

Application Number
CN202411281850.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-27
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

The amount of existing composite nano early strength agents is high, and the strength promotion effect is weakened after 1d of concrete, and even the problem of inverted strength may occur.

Method used

Using the preparation method of ultra-low doping composite nano-premature strength agent, nano-silicon sol and silane-modified polycarboxylic acid are mixed, the pH value is adjusted and the silicon source is added dropwise to form a stable suspension to achieve nano-hydrated calcium silicate. Firm connection with C-S-H gel improves the early and late strength of concrete.

Benefits of technology

Achieve excellent early strength effect under ultra-low doping conditions, while significantly improving the later strength of concrete and reducing production costs. It is suitable for large-scale promotion and industrial production, with environmental benefits and economic value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192595A_ABST
    Figure CN119192595A_ABST
Patent Text Reader

Abstract

The invention provides an ultralow-dosage composite nano early strength agent and a preparation method thereof.The preparation method of the ultralow-dosage composite nano early strength agent comprises the following steps that S1, nano silica sol and silane modified polycarboxylic acid are mixed and stirred, and a suspension A is obtained; s2, adding a calcium source and a dispersing agent into the suspension A, adjusting the pH value to 9-12, and fully stirring to obtain a base material B; s3, dropwise adding a silicon source into the base material B in the S2, shearing and stirring at a high speed, keeping the pH value of a reaction system unchanged, and continuously shearing and stirring at a high speed for 1-2 hours after dropwise adding is finished, so as to obtain the ultralow-dosage composite nano early strength agent. The ultralow-dosage composite nano early strength agent can achieve an excellent early strength effect under the ultralow-dosage condition, and meanwhile, the later strength of concrete can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building material concrete, and in particular to an ultra-low dosage composite nano early strength agent and a preparation method thereof. Background Art

[0002] With the efficient and green development of the construction industry, the prefabricated construction industry, which has the advantages of energy conservation and environmental protection, has developed rapidly. As the main body of prefabricated buildings, precast concrete, mainly prefabricated components, subway segments, pipe piles and other products, has also begun to develop rapidly. Precast concrete has high standards for structure and appearance. At the same time, in order to achieve perfect splicing of all precast concrete, a fixed steel mold is generally required as a mold during production. In order to improve production efficiency, accelerate mold turnover, minimize construction cycle, and maximize benefits, the requirements for the early strength development of concrete are also getting higher and higher.

[0003] There are usually two ways to improve early strength: one is to use chemical admixtures to accelerate the hydration of Portland cement; the other is to steam cure precast concrete components to improve early strength. However, steam curing not only consumes a lot of energy, but also damages the later strength and durability of concrete. As an admixture that can accelerate the development of early strength of concrete, early strength agent is increasingly needed in engineering.

[0004] Nano CSH early strength agent has gradually become a research hotspot in the field of early strength agent due to its large specific surface area and excellent early strength effect. For example, Chinese patent CN 113979661 A discloses a method for preparing a nano calcium silicate suspension with high stability and good early strength effect. Hydroxyl and amine groups are introduced into the molecular structure of the dispersant. Hydroxyl hydrogen or amine hydrogen can form hydrogen bonds with silicon atoms to prepare a nano CSH early strength agent with high stability and excellent early strength performance. The dosage is 2%-4% of the cementitious material. Chinese patent CN 107235650A discloses a water-based nano-composite early strength admixture and its preparation method. The preparation process is simple, the product stability is good, and the early strength of concrete can be effectively improved. The 12h and 24h mortar compressive strengths are increased by 30% and 16% respectively compared with the ordinary commercially available early strength polycarboxylate water-reducing agent, and the later strength is not affected. Zhang Chaoyang et al. (Effect of Nano-CSH on Cement Hydration, Pore Structure of Hardened Paste and Concrete Strength [J], 2019, 47(5), 585-593) reported a method for synthesizing nano-CSH gel and prepared a CSH gel suspension with a solid content of 10% which had a significant promoting effect, but had a significant negative impact on the concrete strength after 1 day.

[0005] The above patents and papers generally adopt the coprecipitation method to prepare nano CSH suspension, which basically solves the problem of suspension stability and has a significant early strength promotion effect. However, in its actual application, the dosage of nano CSH is relatively high, often up to 2%-4% of the cementitious material; at the same time, the promotion effect of nano CSH suspension on the strength of concrete after 1 day is significantly weakened, and even at 28 days, problems such as strength shrinkage may occur.

[0006] Chinese patent CN112830710A "A coupling agent modified nano calcium silicate hydrate crystal nucleus early strength agent and its preparation method" discloses a method of using a coupling agent to chemically bond the inorganic compound calcium silicate hydrate with an organic dispersant. One end of the coupling agent reacts with the calcium silicate hydrate and the other end reacts with the dispersant to improve the dispersion of the CSH crystal nucleus and inhibit the growth of the CSH crystal nucleus. At a lower dosage, it can provide more effective specific surface area and obtain a better early strength effect. However, its dosage is still relatively high and the early strength effect still needs to be further improved.

[0007] Therefore, it is of great significance to provide an ultra-low dosage composite nano early strength agent with low dosage and excellent early strength effect and a preparation method thereof. Summary of the invention

[0008] In view of the fact that the dosage of existing composite nano early strength agents is still relatively high and the early strength effect still needs to be further improved, the present invention provides an ultra-low dosage composite nano early strength agent and a preparation method thereof. The ultra-low dosage composite nano early strength agent can achieve excellent early strength effect under ultra-low dosage conditions and can significantly improve the later strength of concrete.

[0009] To achieve the above object, the technical solution adopted by the present invention is:

[0010] A method for preparing an ultra-low dosage composite nano early strength agent comprises the following steps:

[0011] S1. The nano-silica sol and the silane-modified polycarboxylic acid are mixed and stirred to obtain a suspension A;

[0012] S2. Add the calcium source and dispersant to the suspension A, adjust the pH to 9-12, stir well, and obtain the base material B;

[0013] S3. Add the silicon source dropwise into the base material B described in S2, stir at high speed, and maintain the pH value of the reaction system unchanged. After the addition is completed, continue stirring at high speed for 1-2 hours to obtain the ultra-low dosage composite nano early strength agent.

[0014] Furthermore, the silane-modified polycarboxylic acid is prepared by the following method:

[0015] Step 1: Heat the polyether macromonomer, alkoxysilane and deionized water in a water bath, stir and dissolve them, and set aside;

[0016] Step 2: Prepare liquid A by mixing unsaturated carboxylic acid, reducing agent, chain transfer agent and deionized water; prepare liquid B by mixing initiator and deionized water for later use;

[0017] Step 3: Add solution A and solution B obtained in step 2 to the mixed solution obtained in step 1 under continuous water bath heating. The total adding time is 2-2.5 hours. After the adding is completed, the water bath heating is maintained for continuous reaction for 6-8 hours. Cool to room temperature to obtain silane-modified polycarboxylic acid.

[0018] Furthermore, the mass ratio of the polyether macromonomer, alkoxysilane and deionized water is (200-220):(8-10):(100-120);

[0019] The mass ratio of the unsaturated carboxylic acid, the reducing agent, the chain transfer agent and the deionized water is (18-26):(0.5-0.8):(0.8-1.2):(50-70);

[0020] The mass ratio of the initiator to deionized water is (2-2.6):(50-60);

[0021] The water bath heating temperature is 40-75°C.

[0022] Furthermore, the polyether macromonomer is an isopentanol polyoxyethylene ether macromonomer having a number average molecular weight of 2400;

[0023] The unsaturated carboxylic acid is one or more of acrylic acid, methacrylic acid, maleic anhydride, fumaric acid and derivatives thereof;

[0024] The initiator is one or more of ammonium persulfate, sodium persulfate, tert-butyl peroxyvalerate, and dicyclohexyl peroxydicarbonate;

[0025] The reducing agent is one or more of L-ascorbic acid, sodium bisulfite, ferrous sulfate, potassium bisulfite, and sodium hypophosphite;

[0026] The chain transfer agent is one or more of thioglycolic acid, mercaptopropionic acid, sodium methacrylic acid, and mercaptoethanol;

[0027] The alkoxysilane is one or more of γ-methacryloxypropyltrimethoxysilane, vinylmethyldimethoxysilane, vinyltriethoxysilane and vinyldimethylethoxysilane.

[0028] Further, the calcium source is one or more of calcium nitrate tetrahydrate, calcium formate, calcium gluconate, calcium acetate, calcium nitrite, and calcium dihydrogen phosphate;

[0029] The silicon source is one or more of sodium metasilicate pentahydrate, sodium metasilicate nonahydrate, sodium fluorosilicate, and potassium silicate;

[0030] The dispersant is one or more of sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide and gum arabic.

[0031] Furthermore, the stirring temperature in S1 is 20-40°C, the rotation speed is 600r / min, and the time is 3h.

[0032] Furthermore, the pH adjustment in S2 is to adjust the pH value by using a 30% by mass NaOH solution and HNO3; the sufficient stirring temperature in S2 is 15-20°C, the rotation speed is 600r / min, and the time is 0.5-1h.

[0033] Furthermore, the dripping acceleration rate in S3 is 0.8-1.6 mL / min, the high-speed shear stirring temperature in S3 is 5-20° C., and the rotation speed is 2000-5000 r / min.

[0034] Furthermore, the weight ratio of the nano-silica sol, silane-modified polycarboxylic acid, calcium source, dispersant, and silicon source is (60-100):(180-220):(76-120):(20-40):(100-158); the concentration of the calcium source is 2-4 mol / L; the concentration of the silicon source is 1.7-3.2 mol / L; the molar ratio of calcium element to silicon element in the calcium source and silicon source is (1.6-2.0):1.

[0035] Another object of the present invention is to provide an ultra-low dosage composite nano early strength agent.

[0036] An ultra-low dosage composite nano early strength agent is prepared according to any of the above-mentioned preparation methods.

[0037] Another object of the present invention is to provide an application of an ultra-low dosage composite nano early strength agent.

[0038] An application of the above-mentioned ultra-low dosage composite nano early strength agent in cement concrete.

[0039] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0040] The invention provides a preparation method of an ultra-low dosage composite nano early strength agent. The method comprises the following steps: firstly reacting silane-modified polycarboxylic acid with nano silica sol, polycondensing Si-OH functional groups on the side chains of the silane-modified polycarboxylic acid with Si-OH on the surface of the nano silica sol to form reliable chemical bonding, and obtaining a stable suspension A; subsequently, fully mixing a calcium source with the suspension A, adjusting the pH to 9-12, fully ionizing the carboxylate radicals on the main chain of the polycarboxylic acid, fully complexing free calcium ions in the solution through electrostatic action, controlling the calcium ions to be at a suitable supersaturation, separating nucleation and growth stages, and then dripping a silicon source to make the particle size of the generated nano calcium silicate hydrate as small as possible; since H atoms on the main chain of the PCE are closer to the surface, hydrogen bonds can be formed with a large number of oxygen atom sites provided by a CSH gel, and a firm connection between the nano silica sol and the CSH can be achieved while stabilizing the CSH.

[0041] The ultra-low dosage composite nano early strength agent prepared by the present invention stably disperses nano silica sol and CSH gel through silane-modified polycarboxylic acid, and realizes reliable connection between the two. On the one hand, nano CSH can provide a large number of heterogeneous nucleation sites for cement hydration, and form a high ion concentration gradient on its surface, promote the precipitation of hydration products, and achieve excellent early strength effect. On the other hand, the nano silica sol connected to the silane side chain reacts with the alkaline solution released by cement hydration to increase the amount of hydration products, and cooperates with nano CSH to further improve the early strength of concrete. It achieves excellent early strength effect under ultra-low dosage conditions, and can significantly improve the later strength of concrete.

[0042] The invention provides a preparation method of an ultra-low dosage composite nano early strength agent, which is simple and easy to operate, can significantly reduce production costs, is suitable for large-scale promotion and industrial production, shows significant environmental benefits and economic value, and has positive significance for promoting the sustainable development of the construction industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] The invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.

[0044] Figure 1 It is a schematic diagram of the microstructure of the ultra-low dosage composite nano early strength agent of the present application. DETAILED DESCRIPTION

[0045] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention is further described by the following examples. Obviously, the following examples are only part of the embodiments of the present invention, rather than all the embodiments; it should be understood that the embodiments of the present invention are only used to illustrate the technical effects of the present invention, rather than to limit the scope of protection of the present invention.

[0046] The raw materials in the examples can all be obtained commercially; unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0047] Example 1

[0048] A method for preparing an ultra-low dosage composite nano early strength agent comprises the following steps:

[0049] Preparation of silane-modified polycarboxylic acid:

[0050] Step 1: Place 200 parts by weight of a prenol polyoxyethylene ether macromonomer with a molecular weight of 2400, 8 parts by weight of γ-methacryloxypropyltrimethoxysilane and 120 parts by weight of deionized water in a four-necked flask, heat in a water bath at 55° C., stir to dissolve, and set aside;

[0051] Step 2: 20 parts by weight of acrylic acid, 0.5 parts by weight of ascorbic acid, 0.8 parts by weight of thioglycolic acid and 50 parts by weight of deionized water are prepared into liquid A; 2 parts by weight of H2O2 and 50 parts by weight are prepared into liquid B for standby use;

[0052] Step 3: Add solution A and solution B obtained in step 2 to the mixed solution obtained in step 1 at the same time under continuous water bath heating at 55°C. The total adding time is 2 hours. After the adding is completed, the water bath heating is maintained for continuous reaction for 7 hours. Cool to room temperature to obtain silane-modified polycarboxylic acid.

[0053] S1. 75 g of nano-silica sol was mixed with 180 g of silane-modified polycarboxylic acid and stirred at 25 ° C and 600 r / min for 3 h to obtain a suspension A;

[0054] S2. 106.2 g of calcium nitrate tetrahydrate, 480 g of deionized water and 10 g of gum arabic were added to 113.6 g of suspension A, the pH value was adjusted to 12 by 30% NaOH solution and HNO3 by mass fraction, and the mixture was stirred at 18 ° C and 600 r / min for 1 h to obtain base material B;

[0055] S3. Add 83.2g of sodium silicate nonahydrate and 120g of deionized water to the base material B in S2 at a rate of 0.8mL / min, stir at a high speed of 18°C ​​and 3000r / min, and maintain the pH value of the reaction system unchanged. After the addition is completed, continue high-speed shear stirring for 2h to obtain the ultra-low dosage composite nano early strength agent.

[0056] Example 2

[0057] A method for preparing an ultra-low dosage composite nano early strength agent comprises the following steps:

[0058] Preparation of silane-modified polycarboxylic acid:

[0059] Step 1: Place 200 parts by weight of a prenol polyoxyethylene ether macromonomer with a molecular weight of 2400, 10 parts by weight of γ-methacryloxypropyltrimethoxysilane and 120 parts by weight of deionized water in a four-necked flask, heat in a water bath at 65° C., stir to dissolve, and set aside;

[0060] Step 2: Prepare liquid A by mixing 22 parts by weight of acrylic acid, 0.6 parts by weight of ascorbic acid, 0.9 parts by weight of thioglycolic acid and 70 parts by weight of deionized water; prepare liquid B by mixing 2.2 parts by weight of H2O2 and 60 parts by weight for standby use;

[0061] Step 3: Add solution A and solution B obtained in step 2 to the mixed solution obtained in step 1 under continuous water bath heating at 65°C. The total adding time is 2.5 hours. After the adding is completed, the water bath heating is maintained for continuous reaction for 8 hours. Cool to room temperature to obtain silane-modified polycarboxylic acid.

[0062] S1. 80 g of nano-silica sol was mixed with 200 g of silane-modified polycarboxylic acid and stirred at 25 ° C and 600 r / min for 3 h to obtain a suspension A;

[0063] S2. 129.8 g of calcium nitrate tetrahydrate, 580 g of deionized water and 15 g of gum arabic were added to 135.2 g of suspension A, the pH value was adjusted to 11.7 by 30% NaOH solution and HNO3 by mass fraction, and the mixture was stirred at 20 ° C and 600 r / min for 0.5 h to obtain base material B;

[0064] S3. Add 83.2g of sodium silicate nonahydrate and 120g of deionized water to the base material B in S2 at a rate of 0.8mL / min, and stir at a high speed of 18°C ​​and 3500r / min, and maintain the pH value of the reaction system unchanged. After the addition is completed, continue high-speed shear stirring for 2h to obtain the ultra-low dosage composite nano early strength agent.

[0065] Example 3

[0066] A method for preparing an ultra-low dosage composite nano early strength agent comprises the following steps:

[0067] Preparation of silane-modified polycarboxylic acid:

[0068] Step 1, put 220 parts by weight of isopentanol polyoxyethylene ether macromonomer with a molecular weight of 2400, 10 parts by weight of γ-methacryloxypropyltrimethoxysilane and 120 parts by weight of deionized water into a four-necked flask, heat in a water bath at 45° C., stir to dissolve, and set aside;

[0069] Step 2: 20 parts by weight of acrylic acid, 0.5 parts by weight of ascorbic acid, 0.8 parts by weight of thioglycolic acid and 70 parts by weight of deionized water are configured into liquid A; 2.1 parts by weight of H2O2 and 50 parts by weight are configured into liquid B for standby use;

[0070] Step 3: Add solution A and solution B obtained in step 2 to the mixed solution obtained in step 1 under continuous water bath heating at 45°C. The total adding time is 2.5 hours. After the adding is completed, the water bath heating is maintained for continuous reaction for 8 hours. Cool to room temperature to obtain silane-modified polycarboxylic acid.

[0071] S1. 90 g of nano-silica sol was mixed with 220 g of silane-modified polycarboxylic acid and stirred at 25 ° C and 600 r / min for 3 h to obtain a suspension A;

[0072] S2. 106.2 g of calcium nitrate tetrahydrate, 480 g of deionized water and 10 g of gum arabic were added to 113.6 g of suspension A, the pH value was adjusted to 11.7 by 30% NaOH solution and HNO3 by mass fraction, and the mixture was stirred at 18 ° C and 600 r / min for 1 h to obtain base material B;

[0073] S3. 83.2 g of sodium silicate nonahydrate and 120 g of deionized water are uniformly added dropwise to the base material B described in S2 at a rate of 1.0 mL / min, and high-speed shear stirring is performed at 15°C and 4000 r / min, and the pH value of the reaction system is maintained unchanged. After the addition is completed, high-speed shear stirring is continued for 1.5 hours to obtain the ultra-low dosage composite nano early strength agent.

[0074] Comparative Example 1

[0075] A method for preparing a composite nano early strength agent comprises the following steps:

[0076] S1. 75 g of nano-silica sol was mixed with 180 g of ordinary polycarboxylic acid and stirred at 25 ° C and 600 r / min for 3 h to obtain a suspension A;

[0077] S2. 106.2 g of calcium nitrate tetrahydrate, 480 g of deionized water and 10 g of gum arabic were added to 113.6 g of suspension A, the pH value was adjusted to 12 by 30% NaOH solution and HNO3 by mass fraction, and the mixture was stirred at 18 ° C and 600 r / min for 1 h to obtain base material B;

[0078] S3. Add 83.2g of sodium silicate nonahydrate and 120g of deionized water to the base material B in S2 at a uniform rate of 0.8mL / min, stir at a high speed of 18°C ​​and 3000r / min, and maintain the pH value of the reaction system unchanged. After the addition is completed, continue high-speed shear stirring for 2h to obtain the composite nano early strength agent.

[0079] Compared with Example 1, this comparative example uses common polycarboxylic acid instead of silane-modified polycarboxylic acid.

[0080] Comparative Example 2

[0081] A method for preparing a composite nano early strength agent comprises the following steps:

[0082] Preparation of silane-modified polycarboxylic acid:

[0083] Step 1: Place 200 parts by weight of a prenol polyoxyethylene ether macromonomer with a molecular weight of 2400, 8 parts by weight of γ-methacryloxypropyltrimethoxysilane and 120 parts by weight of deionized water in a four-necked flask, heat in a water bath at 55° C., stir to dissolve, and set aside;

[0084] Step 2: 20 parts by weight of acrylic acid, 0.5 parts by weight of ascorbic acid, 0.8 parts by weight of thioglycolic acid and 50 parts by weight of deionized water are prepared into liquid A; 2 parts by weight of H2O2 and 50 parts by weight are prepared into liquid B for standby use;

[0085] Step 3: Add solution A and solution B obtained in step 2 to the mixed solution obtained in step 1 at the same time under continuous water bath heating at 55°C. The total adding time is 2 hours. After the adding is completed, the water bath heating is maintained for continuous reaction for 7 hours. Cool to room temperature to obtain silane-modified polycarboxylic acid.

[0086] S1. 75 g of nano-silica sol was mixed with 180 g of silane-modified polycarboxylic acid and stirred at 25 ° C and 600 r / min for 3 h to obtain a suspension A;

[0087] S2. 106.2 g of calcium nitrate tetrahydrate and 480 g of deionized water were added to 113.6 g of suspension A, and the pH value was adjusted to 12 by 30% NaOH solution and HNO3 by mass fraction, and stirred at 18 ° C and 600 r / min for 1 h to obtain base material B;

[0088] S3. Add 83.2g of sodium silicate nonahydrate and 120g of deionized water to the base material B in S2 at a uniform rate of 0.8mL / min, stir at a high speed of 18°C ​​and 3000r / min, and maintain the pH value of the reaction system unchanged. After the addition is completed, continue high-speed shear stirring for 2h to obtain the composite nano early strength agent.

[0089] Compared with Example 1, no additional dispersant is added in step S2 of this comparative example.

[0090] Comparative Example 3

[0091] A nano CSH crystal nucleus early strength agent from a certain manufacturer on the market was used, specifically: BASF Masterset ACE100 early strength agent.

[0092] Comparative Example 4

[0093] A method for preparing a composite nano early strength agent comprises the following steps:

[0094] Preparation of silane-modified polycarboxylic acid:

[0095] Step 1: Place 200 parts by weight of a prenol polyoxyethylene ether macromonomer with a molecular weight of 2400, 8 parts by weight of γ-methacryloxypropyltrimethoxysilane and 120 parts by weight of deionized water in a four-necked flask, heat in a water bath at 55° C., stir to dissolve, and set aside;

[0096] Step 2: 20 parts by weight of acrylic acid, 0.5 parts by weight of ascorbic acid, 0.8 parts by weight of thioglycolic acid and 50 parts by weight of deionized water are prepared into liquid A; 2 parts by weight of H2O2 and 50 parts by weight are prepared into liquid B for standby use;

[0097] Step 3: Add solution A and solution B obtained in step 2 to the mixed solution obtained in step 1 at the same time under continuous water bath heating at 55°C. The total adding time is 2 hours. After the adding is completed, the water bath heating is maintained for continuous reaction for 7 hours. Cool to room temperature to obtain silane-modified polycarboxylic acid.

[0098] S1. 75 g of nano-silica sol was mixed with 180 g of silane-modified polycarboxylic acid and stirred at 25 ° C and 600 r / min for 3 h to obtain a suspension A;

[0099] S2. 106.2 g of calcium nitrate tetrahydrate, 480 g of deionized water and 10 g of gum arabic were added to 113.6 g of suspension A, and stirred at 18 ° C and 600 r / min for 1 h to obtain base material B;

[0100] S3. Add 83.2g of sodium silicate nonahydrate and 120g of deionized water to the base material B in S2 at a uniform rate of 0.8mL / min, stir at a high speed of 18°C ​​and 3000r / min, and maintain the pH value of the reaction system unchanged. After the addition is completed, continue high-speed shear stirring for 2h to obtain the composite nano early strength agent.

[0101] Compared with Example 1, the pH value was not adjusted in this comparative example.

[0102] The above embodiments and comparative examples were subjected to performance tests, and the experimental test methods were as follows:

[0103] The above examples and comparative examples were tested for cement mortar strength using the GB / T17671-1999 "Test Method for Cement Mortar Strength (ISO Method)" standard and the method guided by ASTMC109, wherein the admixture dosages were all solid dosages.

[0104] In Comparative Example 4, since the pH value was not adjusted, the prepared suspension was easily precipitated, a stable sample could not be obtained, and the enhancement effect was significantly weakened, so it was not tested.

[0105] The result is as follows:

[0106] Table 1 Cement mortar test of the embodiment and comparative example

[0107]

[0108] The blank group is a blank experiment without adding any early strength additive. The examples, comparative examples and blank group all use reference cement for the experiments and perform curing under standard curing conditions.

[0109] It can be seen from Table 1 that the cement concrete to which the ultra-low dosage composite nano early strength agent prepared in Examples 1-3 of the present invention is applied has significantly stronger 3d and 28d compressive strength than the blank group and the other comparative examples, which indicates that the composite nano early strength agent prepared under the appropriate calcium-silicon ratio, dispersant, polycarboxylate water-reducing agent and synthesis process conditions described in the present invention can significantly improve the compressive strength of cement concrete at various ages, such as early and late stages, so that it can meet the strength requirements of various engineering applications.

[0110] However, since ordinary polycarboxylic acid is used instead of silane-modified polycarboxylic acid in Comparative Example 1, the late strength of the concrete is insufficient, and the 28d compressive strength is only 56.98MPa; since no dispersant is added in Comparative Example 2, the stability is poor, and the early strength of the concrete is insufficient, and the 1d compressive strength is only 21.18MPa; Comparative Example 3 is a commercially available early strength agent, which has a strong comprehensive early strength effect, but the improvement in the late strength of the concrete is far less than that of the embodiments.

[0111] In summary, the present invention first reacts silane-modified polycarboxylic acid with nano silica sol, then fully mixes the calcium source with suspension A, adjusts the pH to 9-12, and then drips the ultra-low dosage composite nano early strength agent prepared by the silicon source, stably disperses the nano silica sol and CSH gel through the silane-modified polycarboxylic acid, and realizes a reliable connection between the two. On the one hand, nano CSH can provide a large number of heterogeneous nucleation sites for cement hydration, and form a higher ion concentration gradient on its surface, promote the precipitation of hydration products, and achieve excellent early strength. On the other hand, the nano silica sol connected to the silane side chain reacts with the alkaline solution released by cement hydration to increase the amount of hydration products, and cooperates with nano CSH to further improve the early strength of concrete. Under ultra-low dosage conditions, it has an excellent early strength effect and can significantly improve the later strength of concrete. The preparation method of the ultra-low dosage composite nano early strength agent is simple and easy to operate, can significantly reduce production costs, is suitable for large-scale promotion and industrial production, shows significant environmental benefits and economic value, and has positive significance for promoting the sustainable development of the construction industry.

[0112] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing an ultra-low dosage composite nano early strength agent, characterized in that: The following steps are involved: S1. The nano-silica sol and the silane-modified polycarboxylic acid are mixed and stirred to obtain a suspension A; S2. Add the calcium source and dispersant to the suspension A, adjust the pH to 9-12, stir well, and obtain the base material B; S3. Add the silicon source dropwise into the base material B described in S2, stir at high speed, and maintain the pH value of the reaction system unchanged. After the addition is completed, continue stirring at high speed for 1-2 hours to obtain the ultra-low dosage composite nano early strength agent.

2. A method for preparing the ultra-low dosage composite nano early strength agent according to claim 1, characterized in that: The silane-modified polycarboxylic acid is prepared by the following method: Step 1: Heat the polyether macromonomer, alkoxysilane and deionized water in a water bath, stir and dissolve them, and set aside; Step 2: Prepare liquid A by mixing unsaturated carboxylic acid, reducing agent, chain transfer agent and deionized water; prepare liquid B by mixing initiator and deionized water for later use; Step 3: Add solution A and solution B obtained in step 2 to the mixed solution obtained in step 1 under continuous water bath heating. The total adding time is 2-2.5 hours. After the adding is completed, the water bath heating is maintained for continuous reaction for 6-8 hours. Cool to room temperature to obtain silane-modified polycarboxylic acid.

3. A method for preparing the ultra-low dosage composite nano early strength agent according to claim 2, characterized in that: The mass ratio of the polyether macromonomer, alkoxysilane and deionized water is (200-220):(8-10):(100-120); The mass ratio of the unsaturated carboxylic acid, the reducing agent, the chain transfer agent and the deionized water is (18-26):(0.5-0.8):(0.8-1.2):(50-70); The mass ratio of the initiator to deionized water is (2-2.6):(50-60); The water bath heating temperature is 40-75°C.

4. A method for preparing the ultra-low dosage composite nano early strength agent according to claim 2, characterized in that: The polyether macromonomer is an isopentanol polyoxyethylene ether macromonomer with a number average molecular weight of 2400; The unsaturated carboxylic acid is one or more of acrylic acid, methacrylic acid, maleic anhydride, fumaric acid and derivatives thereof; The initiator is one or more of ammonium persulfate, sodium persulfate, tert-butyl peroxyvalerate, and dicyclohexyl peroxydicarbonate; The reducing agent is one or more of L-ascorbic acid, sodium bisulfite, ferrous sulfate, potassium bisulfite, and sodium hypophosphite; The chain transfer agent is one or more of thioglycolic acid, mercaptopropionic acid, sodium methacrylic acid, and mercaptoethanol; The alkoxysilane is one or more of γ-methacryloxypropyltrimethoxysilane, vinylmethyldimethoxysilane, vinyltriethoxysilane and vinyldimethylethoxysilane.

5. A method for preparing the ultra-low dosage composite nano early strength agent according to claim 1, characterized in that: The calcium source is one or more of calcium nitrate tetrahydrate, calcium formate, calcium gluconate, calcium acetate, calcium nitrite, and calcium dihydrogen phosphate; The silicon source is one or more of sodium metasilicate pentahydrate, sodium metasilicate nonahydrate, sodium fluorosilicate, and potassium silicate; The dispersant is one or more of sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide and gum arabic.

6. A method for preparing the ultra-low dosage composite nano early strength agent according to claim 1, characterized in that: The stirring temperature in S1 is 20-40°C, the rotation speed is 600r / min, and the time is 3h.

7. A method for preparing the ultra-low dosage composite nano early strength agent according to claim 1, characterized in that: The pH adjustment in S2 is to adjust the pH value by using a 30% by mass NaOH solution and HNO3; the sufficient stirring temperature in S2 is 15-20°C, the rotation speed is 600r / min, and the time is 0.5-1h.

8. A method for preparing the ultra-low dosage composite nano early strength agent according to claim 1, characterized in that: The drop acceleration rate of S3 is 0.8-1.6 mL / min, the high-speed shear stirring temperature of S3 is 5-20° C., and the rotation speed is 2000-5000 r / min.

9. A method for preparing the ultra-low dosage composite nano early strength agent according to claim 1, characterized in that: The weight ratio of the nano-silica sol, silane-modified polycarboxylic acid, calcium source, dispersant and silicon source is (60-100):(180-220):(76-120):(20-40):(100-158); the concentration of the calcium source is 2-4 mol / L; the concentration of the silicon source is 1.7-3.2 mol / L; the molar ratio of calcium element to silicon element in the calcium source and silicon source is (1.6-2.0):

1.

10. An ultra-low dosage composite nano early strength agent, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Nano seed crystal early strength agent and preparation method thereof

    CN108751785A

  • Calcium silicate hydrate crystal nucleus early-strength polycarboxylic acid water reducer and preparation method thereof

    CN114014991A

  • Seed crystal type polycarboxylate superplasticizer for prefabricated part and preparation method of seed crystal type polycarboxylate superplasticizer

    CN114316289A

  • Nano-reinforced engineering cement-based composite material and preparation method thereof

    CN115403334A

  • Coagulating early strength agent, preparation method thereof and concrete composition

    CN115893895A

Cited By

  • Liquid cement reinforcing agent and preparation method thereof

    CN121517138A

  • A liquid cement enhancer and method of making same

    CN121517138B